Role of flow velocity and transient hyperemic response evaluated by transcranial doppler for assesing brain autoregulation in mild traumatic brain injury: a case report - Demoina, I Gede Patria; Wiryana, Made; Suarjaya, Putu Pramana; Pradhana, Adinda Putra (DiscoverSys Inc., 2019)
Head injuries are a common case throughout the world, based on data from the Centers for Disease Control, emergency cases, hospitalization cases, and also deaths due to head injuries have increased in the decade 2001-2010. Cerebral autoregulation (CA) is a mechanism for cerebral blood flow (CBF) regulation if there is a change from cerebral perfusion pressure (CPP). The mechanism of brain autoregulation is negative feedback that holds back the increase in mean arterial pressure (MAP) by reducing the diameter of blood vessels so that CBF returns to normal, whereas if MAP falls, brain autoregulation tends to widen blood vessel diameter so that CBF is normal. Transcranial doppler examination can be one of the modalities of investigation that is very useful in patients with head injuries. Transcranial doppler in patients with a head injury can be used to measure mean flow velocity of cerebral artery media and transient hyperemic response test, both of which can assess the prognosis of a course of head injury.